An Inversion-Free Robust Power-Flow Algorithm for Microgrids - Kumar A.; Das S.; Mallipeddi R. (My University, 2025)
Recently, several numerical algorithms have been proposed to solve the power flow (PF) problems of islanded microgrids (MGs). However, these algorithms approximate the steady-state model of the distributed generation units (DGs) as linear equations. In some cases, this linear approximation leads to inaccurate PF solutions due to dead-zone and generation limits of the given DGs. To fill this gap, we propose a new non-linear approximation of the steady-state model of the DGs considering dead-zone and generation limits of the DG. Besides, an inversion-free PF algorithm based on the improved Newton-Traub composition (INTC) is proposed for solving PF problems of grid-connected and islanded MGs more robustly and accurately, where the inverse of the Jacobian matrix is updated by using the Broyden's method. To include the power losses of the neutral conductor and grounding resistance, four-conductor based PF formulation is proposed. The numerical results on several test systems suggest that the proposed algorithm can provide an accurate steady-state solution as compared to other state-of-the-art algorithms. © 2010-2012 IEEE.